2009
DOI: 10.1038/ijo.2009.252
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and anxiety disorders in the population: a systematic review and meta-analysis

Abstract: Anxiety disorders are the most prevalent mental disorders in developed countries. Obesity is hypothesized to be a risk factor for anxiety disorders but evidence supporting an association between these two conditions is not clear. The objectives of this paper were to systematically review the literature for a link between obesity and anxiety disorders in the general population, and to present a pooled estimate of association. We performed a systematic search for epidemiological articles reporting on obesity (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
401
7
28

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(461 citation statements)
references
References 78 publications
(138 reference statements)
25
401
7
28
Order By: Relevance
“…Comorbidity with anxiety and depression has been reported in obesity (Gariepy, Nitka, & Schmitz, 2010;de Wit et al, 2010) and may have influenced performance on the mental flexibility task. ANOVAs revealed significant differences between obese patients with binge eating disorder and controls on all self-rating scales (Table 1).…”
Section: Measures Questionnairesmentioning
confidence: 99%
“…Comorbidity with anxiety and depression has been reported in obesity (Gariepy, Nitka, & Schmitz, 2010;de Wit et al, 2010) and may have influenced performance on the mental flexibility task. ANOVAs revealed significant differences between obese patients with binge eating disorder and controls on all self-rating scales (Table 1).…”
Section: Measures Questionnairesmentioning
confidence: 99%
“…In line with this, de Wit et al (2009) and Zhao et al (2009) found a U-curved association between depression and Body Mass Index (BMI). Although it has been less studied, there is also evidence for an association between anxiety and obesity (Gariepy et al, 2010). Both weight gain and loss are associated with elevated health risks (Must et al, 1999;Newman et al, 2001;Field et al, 2001;Adams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The specific factors producing this association are not well defined. Some studies emphasize the role of psychological distress related to a negative judgment of the environment, feelings of exclusion typical to obese patients that can increase anxiety leading to Panic Disorder [54,55]. In our sample, the relationship with eating behavior shows a prevalence of binge, grazing and nocturnal eating which are all considered maladaptive behaviors.…”
Section: Generalized Anxiety Disorder: Gadmentioning
confidence: 85%